Utilization of agricultural by-products as livestock feeds in Africa. Proceedings of a workshop - Little, D.A.; Said, A.N. (International Livestock Centre for Africa, 1987)
Presents results of studies on the utilization of agricultural by-products as livestock feeds in Africa. Discusses methods of estimating the nutritive value of fibre residues and feed legumes, feed intake and digestibility, prospects of utilizing urea-treated maize stover, agroindustrial by-products and the chemical analysis of feeds.